Numerical and experimental analysis of rubbing–misalignment mixed fault in a dual-rotor system. (September 2021) - Xie, Wenzhen; Liu, Chao; Wang, Nanfei; Jiang, Dongxiang
Dual-rotor systems are widely used in aero-engines, in which rubbing–misalignment mixed faults are essential, as both are frequently observed and can occur simultaneously due to the harsh working conditions of high temperature, high pressure, and high speed. To analyze the vibration characteristics of such faults, a dual-rotor system model is established and dynamic responses under varying parameters of the dual-rotor system with rubbing–misalignment mixed fault are investigated. Through numerical simulation, the effects of speed ratio, rubbing clearance, and rubbing stiffness on the dual-rotor system with rubbing–misalignment fault are revealed. Meanwhile, experimental tests are conducted for validation, the main findings of which are that the characteristic frequency components could benefit the diagnosis of mixed faults in dual-rotor systems.